Web-Based Citizen Contribution: An Model to Optimize Political Participation in the Legislation Function of the Representative Council - Muhamad Pelengkahu; Najib Satria (Jurnal Kajian Pembaruan Hukum, 2024)
At present, legal products do not reflect public justice; rather, they serve the interests and triumph of political groups or elites that are technical, insubstantial, and short-term. This, of course, significantly interferes with the operation of the government system, which in turn disrupts the stability of society, particularly in terms of legal certainty. The objective of this research is to evaluate and develop a political participation scheme that can effectively engage the community at the grassroots level in the legislative function of the People's Representative Council. In terms of methodology, this research is normative legal research, which is evaluative in nature. Qualitative analysis techniques are employed to analyze secondary data. This reasearch indicate that the laws enacted by the People's Representative Council thus far have not been aspirational. This implies that they have not been able to take into account and implement the aspirations of all societal segments, resulting in their implementation being at odds with the community's desire. Consequently, we suggest the implementation of a web-based system for information, aspirations, and voting, which we refer to as WASIT. The utilization of website media is due to the fact that the internet is a daily necessity for the Indonesian populace. The KOMINFO and DUKCAPIL community have appointed an NGO that is specifically dedicated to legislative supervision to establish this system. NGOs are assigned the responsibility of developing a website with the assistance of KOMINFO. The Directorate General of DUKCAPIL will collect community data by logging in with the Citizen Identity Number.